La clinica invisibile dell’invidia - Aliquò, Maria Chiara; Albrizio, Mariapia; Stocco, Ester (Il sogno della farfalla, 2023)
The aim of this work is to propose an analysis of the concept of envy in the light of Massimo Fagioli’s discoveries. Psychiatric-psychodynamic literature has devoted a large number of works to this dynamic since it has been widely recognized as a fundamental etiopathogenic factor in the development of mental disorders. Firstly, the authors focus on the root of this dynamic, which originates from the death instinct, an unconscious dimension. Secondly, the article explores the different clinical manifestations of envy in the psychotherapeutic relationship. This represents a fundamental challenge for the psychotherapist that can only be faced by having a precise knowledge of this complex dynamic. Through a deep analysis of the dynamic of envy as theorized in the human birth theory, the authors present some psychotherapeutic reflections based on their experience and clinical practice.